Proceedings of the International Conference on Management, Accounting, and Economy (ICMAE 2020) 2020
DOI: 10.2991/aebmr.k.200915.013
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Job Satisfaction, Management Innovation, and Organizational Motivation on Organizational Performance

Abstract: The aim of this study is to assess the impact of job satisfaction, managerial innovation and organizational motivation on the organizational performance of Riau oil companies in Indonesia in the current digital age. The reliability test was based on Cronbach's Alpha, and a correction factor for the total number of corrected items was used to test the internal consistency of the responses to the questionnaire. The ANOVA test can be used to estimate respondents' perceptions of these factors based on the chosen d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
1
2
0
1
Order By: Relevance
“…This result is consistent with previous studies (e.g. Putriyadi et al, 2020;Khosravi et al, 2019;Hashi and Stojčić, 2013) that studied the MI-OP relationship and reported the positive link between them. Moreover, our study contradicts the findings of MagnierWatanabe and Benton (2017) as well as Walker et al (2011).…”
Section: Theoretical and Practical Implicationssupporting
confidence: 93%
See 1 more Smart Citation
“…This result is consistent with previous studies (e.g. Putriyadi et al, 2020;Khosravi et al, 2019;Hashi and Stojčić, 2013) that studied the MI-OP relationship and reported the positive link between them. Moreover, our study contradicts the findings of MagnierWatanabe and Benton (2017) as well as Walker et al (2011).…”
Section: Theoretical and Practical Implicationssupporting
confidence: 93%
“…The Nexus of Management Innovation, Performance Management, and Organizational… 2018; Putriyadi et al, 2020) posit that MI is a significant driver of OP. Based on the lite rature review, we propose the following hypothesis:…”
Section: Literature Review and Hypotheses Development Management Inno...mentioning
confidence: 99%
“…Currently, the demand for digital technology continues to increase, therefore, various products, processes, markets, and innovations have the potential to improve performance [40]. The results of other studies on job satisfaction showed that there is an innovative and motivating relationship with organizational performance, where an increase in achievement can also increase effectiveness, efficiency, productivity, and competitiveness in the digital era [41]. In nursing, digital technology is intended to support healthcare that is Accepted, Effective, and Efficient [42].…”
Section: Discussionmentioning
confidence: 99%
“…Di masa ini, perusahaan harus menjaga karyawan sebagai asset SDM yang harus dimanfaatkan dan dijaga. Dengan mengetahui pengaruh job satisfaction, dapat meningkatkan kemampuan perusahaan sehingga dapat bersaing di era digital yang berkelanjutan di saat ini (Putriyadi et al, 2020).…”
Section: Pendahuluanunclassified